PROGRAM PEMENUHAN ENERGI DI RUMAH QUR’AN SEMBALUN DESA SEMBALUN BUMBUNG, KECAMATAN SEMBALUN, KABUPATEN LOMBOK TIMUR - Yadnya, Made Sutha; Ramadhani, Cipta; Zubaidah, Teti; Kanata, Bulkis; Rosmaliati, Rosmaliati (Jurnal Pepadu, 2025)
Sembalun Bumbung Village, East Lombok, faces the problem of river pollution due to the disposal of livestock manure and garbage, which on the other hand has great potential to be processed into biogas as an economical, environmentally friendly, and sustainable alternative energy. This program aims to design and implement a biogas system at Rumah Qur'an At-Tazkiyyah Sembalun, a boarding school that is also a center for community empowerment, to meet energy needs while reducing environmental pollution. The methods used include training and assistance to students and the community about biogas processing, starting from organic waste fermentation, the use of fermented gas for cooking and electricity, to the use of residual waste as organic fertilizer, as well as education on livestock care and waste management to support the sustainability of the program. Expected outputs include the production of renewable energy in the form of biogas for cooking and electricity, reduction of waste that pollutes the environment, increasing public awareness about waste management, and creating a cleaner and healthier environment. Keyword : livestock manure; garbage; energy; biogas; organic fertilizer